THE ROLE OF THE STATISTICAL INFORMATION SYSTEM IN ASSESSING ENTERPRISE PERFORMANCE - Musurmonova M. O. (Modern American Journals, 2025)
This article explores the significance of the statistical information system in assessing enterprise performance. It discusses how reliable and timely data support economic reforms, effective resource management, and strategic decision-making. The study analyzes the structure and functions of the system, its practical applications, and current challenges such as delays, incomplete reporting, and insufficient digital integration. Scientific and practical recommendations are proposed to improve the system in line with international standards.
Keywords: Statistical information system, enterprise performance, economic analysis, decision-making, data reliability, efficiency.